RONDON PROJECT: REFLECTIONS ON AN EXTRACURRICULAR EXPERIENCE (Fiep Bulletin - online, 2014)
This review aims to analyze the actions implemented by the group of the Physical Education of the Federal University of Pelotas (UFPel) at Rondon Project, 2006 edition, in Paraima city, RR. Among our goals were: to briefly map the sportive culture of the city; to identify and support the sportive agents of the region; to build, with the community support, public politics in the sport, leisure and the physical education. While in town from February 6th and 16th, we lived meaningful cultural experiences for our professional life. Among them, the most relevant were: we were engaged at the municipal conference of sports; the game workshop we provided to the city educators; and the soccer practice at an indigenous community. For this review we used the “observant participation” methodology (Wacquant; 2002). To sum up, we highlight the benefits we, students and professors, and the community earned from the Rondon Project. We also highlight how innovative this project is in the extracurricular activities once nowadays most of them are still based on aid models.
Keywords: extracurricular activities; culture; physical Education